International society of sports nutrition position stand: tactical athlete nutrition - Drew E. Gonzalez; Matthew J. McAllister; Hunter S. Waldman; Arny A. Ferrando; Jill Joyce; Nicholas D. Barringer; J. Jay Dawes; Adam J. Kieffer; Travis Harvey; Chad M. Kerksick; Jeffrey R. Stout; Tim N. Ziegenfuss; et al. (Taylor & Francis Group, 2022)
This position stand aims to provide an evidence-based summary of the energy and nutritional demands of tactical athletes to promote optimal health and performance while keeping in mind the unique challenges faced due to work schedules, job demands, and austere environments. After a critical analysis of the literature, the following nutritional guidelines represent the position of the International Society of Sports Nutrition (ISSN). General Recommendations Nutritional considerations should include the provision and timing of adequate calories, macronutrients, and fluid to meet daily needs as well as strategic nutritional supplementation to improve physical, cognitive, and occupational performance outcomes; reduce risk of injury, obesity, and cardiometabolic disease; reduce the potential for a fatal mistake; and promote occupational readiness. Military Recommendations Energy demands should be met by utilizing the Military Dietary Reference Intakes (MDRIs) established and codified in Army Regulation 40-25. Although research is somewhat limited, military personnel may also benefit from caffeine, creatine monohydrate, essential amino acids, protein, omega-3-fatty acids, beta-alanine, and L-tyrosine supplementation, especially during high-stress conditions. First Responder Recommendations Specific energy needs are unknown and may vary depending on occupation-specific tasks. It is likely the general caloric intake and macronutrient guidelines for recreational athletes or the Acceptable Macronutrient Distribution Ranges for the general healthy adult population may benefit first responders. Strategies such as implementing wellness policies, setting up supportive food environments, encouraging healthier food systems, and using community resources to offer evidence-based nutrition classes are inexpensive and potentially meaningful ways to improve physical activity and diet habits. The following provides a more detailed overview of the literature and recommendations for these populations.